The Effect of AI-Based Digital Teaching Materials on the Motivation and Learning Outcomes of High School Stu-dents - Dian Ariswati; Muhammad Fahreza W; Andi Mulyadi Radjab (International Forum of Researchers and Lecturers, 2026)
This research was designed not only to measure the direct impact of Artificial Intelligence (AI)-based digital teaching materials on motivation and learning outcomes but also to identify the factors influencing the effectiveness of their implementation in the context of a high school in an island area. The objectives of this study are: (1) To determine the significant effect of using Artificial Intelligence (AI)-based digital teaching materials on the learning motivation of Class XII students at SMAN 1 Kepulauan Selayar. And (2) To determine the significant effect of using Artificial Intelligence (AI)-based digital teaching materials on the learning outcomes of Class XII students at SMAN 1 Kepulauan Selayar. This study uses a quantitative approach through an experimental design to test the hypothesis regarding the significant effect of using Artificial Intelligence (AI)-based digital teaching materials on student motivation and learning outcomes in Economics. A sample of 30 Class XII students will be randomly selected. Data collection techniques include Questionnaires, Tests, observation, and documentation. The results of this study indicate (1) A significant and positive effect of the use of Artificial Intelligence (AI)-based digital teaching materials on the learning motivation of Class XII students at SMAN 1 Kepulauan Selayar. (2) The use of Artificial Intelligence (AI)-based digital teaching materials (X) significantly influences Economics learning outcomes (Y2).